The Antecedent of Environmental Attitude - EFFENDI, Mohamad Irhas; SUGANDINI, Dyah; SUKARNO, Agus; KUNDARTO, Muhamad (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.v11.6(46).28, 2020)
This investigation means to examine the impact of environmental awareness, green pro- motion on environmental attitudes mediated by trust. The study was conducted on pro- environment consumers. The number of respondents was 150 college students in a Special Region of Yogyakarta. The data collection method used was a questionnaire, and data analysis using SEM-PLS 3.28 version. The results showed that the environmental awareness and green promotion influence the environmental attitude intervened by a trust. The impact of green promotion on environmental attitude is not significant.